2015
DOI: 10.7567/jjap.54.08kc13
|View full text |Cite
|
Sign up to set email alerts
|

Potential-induced degradation of Cu(In,Ga)Se2photovoltaic modules

Abstract: Potential-induced degradation (PID) of Cu(In,Ga)Se 2 (CIGS) photovoltaic (PV) modules fabricated from integrated submodules is investigated. PID tests were performed by applying a voltage of %1000 V to connected submodule interconnector ribbons at 85°C. The normalized energy conversion efficiency of a standard module decreases to 0.2 after the PID test for 14 days. This reveals that CIGS modules suffer PID under this experimental condition. In contrast, a module with non-alkali glass shows no degradation, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 51 publications
(70 reference statements)
0
74
1
1
Order By: Relevance
“…PID in SHJ PV modules was found to be effectively prevented by the use of an ionomer encapsulant, demonstrating that the high reliability of SHJ PV modules can be further improved by using encapsulants with a high electrical resistance. This protective effect is already well known for preventing PID in other types of PV modules; this effect is in part caused by the suppression of Na migration. The PID‐suppression effect observed in this study is likely caused by a significant reduction in Na migration, which is consistent with the proposed mechanism presented in Section .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…PID in SHJ PV modules was found to be effectively prevented by the use of an ionomer encapsulant, demonstrating that the high reliability of SHJ PV modules can be further improved by using encapsulants with a high electrical resistance. This protective effect is already well known for preventing PID in other types of PV modules; this effect is in part caused by the suppression of Na migration. The PID‐suppression effect observed in this study is likely caused by a significant reduction in Na migration, which is consistent with the proposed mechanism presented in Section .…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that PID in many types of PV modules including p‐type c‐Si, n‐type front‐emitter c‐Si, and CIGS modules can be recovered by applying the opposite bias to that used in the degradation tests. To investigate whether such a regeneration effect occurs for the PID in SHJ PV modules, we applied a positive bias of +1000 V to a degraded module.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations